1986
DOI: 10.1021/ja00285a039
|View full text |Cite
|
Sign up to set email alerts
|

cis-[Bis(dicyclohexylphosphino)ethane]platinum(0) reacts with unactivated carbon-hydrogen bonds

Abstract: 22) Shapley and co-workers have synthesized a trinuclear µ2complex containing a (µ3-1 2-02 2) ligand.48 c/s-[Bis(dicyclohexylphosphino)ethane]platinum(0) Reacts with Unactivated Carbon-Hydrogen Bonds1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 1 publication
(2 reference statements)
0
17
0
Order By: Relevance
“…The computations also show that the singlet-triplet triplet free energy splitting (∆E st ; kcal/mol) for these fragments are in the order: Rea-Ni (23.7) < Rea-Pd (50.1) < Rea-Pt (63.9). These values are much greater than those for other previously studied L 2 M complexes that have various ancillary ligands [51][52][53][54][55][56]. Therefore, it is possible that the oxidative addition reactions (Eq.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The computations also show that the singlet-triplet triplet free energy splitting (∆E st ; kcal/mol) for these fragments are in the order: Rea-Ni (23.7) < Rea-Pd (50.1) < Rea-Pt (63.9). These values are much greater than those for other previously studied L 2 M complexes that have various ancillary ligands [51][52][53][54][55][56]. Therefore, it is possible that the oxidative addition reactions (Eq.…”
mentioning
confidence: 75%
“…The crucial experimental works that are presented in Scheme 1 inspire this study of the potential energy surfaces of these oxidative addition reactions, using density functional theory (DFT). There have been a number of reports concerning the conventional oxidative additions-reductive eliminations of alkanes to low-valence metals, which has led to an understanding of the factors that affect these reactions [51][52][53][54][55][56]. These studies have mostly focused on the catalytic reactions of saturated hydrocarbons to zerovalent group 10 elements (i.e., Ni, Pd, and Pt).…”
Section: Introductionmentioning
confidence: 99%
“…These studies [30][31][32][33][34] , along with parallel, beautiful, studies by Bergman [35] , played a useful role in establishing the facility with which late transition metals could cleave (either intra-or intermolecularly) unactivated aliphatic C-H bonds. These studies were extensive, but involved conceptually straightforward examinations of products: the characterization of C-H bonds by examining the shuffling of deuterium in isotopically labeled species using NMR or mass spectroscopy [30] . Among the interesting outcomes of this work was the realization that cleavage of unactivated CH bonds (e.g., of methane) proceeded very rapidly by reaction with Pt(0) centers in solution (Eq.…”
Section: Intramolecular Reactions In Organoplatinum(ii) Compoundsmentioning
confidence: 97%
“…Reaction of dialkyl(1,5) cyclooctadieneplatinum(II) compounds with supported platinum(0) in the presence of H 2 proceeded by transferring the "Pt(II)R 2 " moiety to the Pt(0) surface, (with the reaction of cyclooctadiene to cycloctane) where it formed surface platinum alkyls with well-defined structures. Isotopic labeling enabled us to follow the subsequent reactions (particularly reactions involving C-H bonds) of these surface alkyls-reactions, rearrangements, isotopic exchange reactions, and others-on the surface [30] .…”
Section: (Eq 4)mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Theoretical and experimental work has shown that this type of oxidative addition and reductive elimination chemistry can be influenced significantly by the auxiliary ligands of the low-valent metals involved. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] A DFT study on the oxidative addition of 1,3-dimethylimidazolium to a palladium centre has shown that an increased thermodynamic driving force exists both for palladium complexes bearing chelated phosphines compared to the associated monodentate phosphines, and for complexes that contain more basic phosphine ligands (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%